The relationship between impulsivity and craving of internet addiction in a clinical sample of adolescents - Uygun, Sabide Duygu; Arı, Demet Aygün; Çetinkaya, Semra (Journal of Dependence, 2022)
Objective: The aim of the study was to examine the relationship of internet addiction and related variables with high-risk personality traits that predict future alcohol and substance use in adolescents and to compare adolescents with and without internet addiction in terms of these personality traits. Method: A cross-sectional design study was adopted in which 196 participants, 161 of whom were males, with a mean age of 16.7 took part. The assessment consisted of a demographic form, and additionally two self-administered instruments including the Substance Use Risk Profile Scale (SURPS) and the Addiction Profile Index Internet Addiction Form (BAPINT). Results: There was a statistically significant relationship between the scores of the craving for the BAPINT and the scores of the impulsivity for the SURPS. In addition, there was a statistically significant relationship between the scores of the effect on life for the BAPINT and the scores of the anxiety sensitivity for the SURPS. Internet addiction was determined in 31.1% (n=61) of the participants using the self-report scale. There was no significant difference in personality traits between adolescents with and without internet addiction, according to the BAPINT scores. Conclusion: Screening and interfering with impulsivity and anxiety sensitivity when assessing internet use in adolescents may protect against internet addiction.